An analysis of modern dental filling (restorative) materials usage at multi-profile private dental clinic - Мочалов, Ю. О. (Actual Dentistry, 2019)
Resume. Today, dental treatment is one of the most widespread types of medical care in Ukraine. During 2017 more than 35 million visits to the dentist were registered in Ukraine, more than 17 million people are in need of dental treatment. The most common dental manipulation in Ukraine is the treatment of caries and its complications. Aim of the study: the analysis of the work of a private dental institution for 5 years in partn of hard teeth`s tissues defects treatment using of modern photopolymer filling (restoration) dental materials. Materials and methods. An electronic database of the Stamil dental clinic from Kyiv for the period 2013–2017 was analyzed, for the subject of frequency and varieties of therapeutic manipulations performed and usage of filling (restoration) materials. Computer programs 1С: Enterprise 7.0, MicroSoft Excel 2016 are used. Results. During the 2013-2017, the most commonly used procedure in the clinic was the restoration of the crown part of the teeth with fillings by 43.03±3.25 % (М = 43.88 %) of the visits. Among the used filling (restoration) materials light curing composite materials prevailed – 87.54±20.7 % (М = 87.36 %) of fillings. A decrease among amount of glass-ionomer fillings was observed – from 12.15 to 9.57 %, reducing the amount of performed artistic dental restoration – from 3.93 to 3,02 %. The introduction of the latest novel nano hybrid composite materials into practice has increased. Materials from the companies «3M-ESPE» (USA-Germany), «VOCO» (Germany), «Ultradent» (USA), «Mani Schutz Dental» (Germany), «Tokuyama Dental Corporation» (Japan) were used. The frequency of use of domestic dental photocomposites «Jen-Radiance» for fillings and artistic restorations has increased (to 59.11 and 32.99 % respectively). This testifies to the possibility of successful implementation of import-replacement programs for domestic stomatology and the development of production and other dental materials and equipment. Key words: stomatology, fillings, photocomposites, application.